IMPLEMENTASI KEBIJAKAN REKRUTMEN DAN SELEKSI CALON ANGGOTA LEGISLATIF PARTAI KEBANGKITAN BANGSA UNTUK PEMILIHAN UMUM 2019 - Muid Djalal; Agustinus B. Pati; Elfie Mingkid; Novie R. Pioh; Evelin J. R. Kawung; Burhan Niode (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2023)
ABSTRACT This research aims to analyze the Implementation of the Recruitment and Selection Policy of Legislative Candidates of the National Awakening Party for the 2019 General Election. This research used a qualitative research design with a descriptive approach conducted at the DPW PKB Office of North Sulawesi Province located in Lingkungan I, Tikala Ares Village, Tikala District, Manado City. Data collection techniques were used through observation, interviews, literature study and qualitative, audio and visual documentation. Data sources consisted of primary data and secondary data. Data analysis techniques used are data reduction, data presentation and conclusion drawing or verification. The results showed that in the aspect of communication, it was still lacking, this was because it was only carried out in 2 electoral districts and carried out at the elite level so that it did not touch directly on the community. The resource aspect, there is a lack of human resources and budget resources, such as at the stage of the process of delivering information to the target recruitment of candidates. The disposition aspect, in policy implementation, the implementers already have a good attitude because they understand the tasks they carry out. While the bureaucratic structure aspect, runs hierarchically through the mechanism of the law and PKB party policy.